Novel complementary Sziklai pair based high gain low noise small-signal amplifiers - Shukla, SachchidaNand; Arshad, Syed Shamroz; Srivastava, Geetika (Institute of Advanced Engineering and Science, 2023)
A new paired configuration of opposite polarity BJTs, the “complementary Sziklai pair” is introduced in the series of multi-BJT-based devices like Darlington and Sziklai pair, and its viability is tested in small-signal common emitter (CE) and common collector (CC) amplifier configurations. The Darlington and Sziklai both face the problem of poor frequency response at a higher frequency which is addressed by the proposed configuration. The proposed pair with CE amplifier holds class-A amplification property with a high voltage gain of 200.05, a high current gain of 11.62, wider bandwidth of 1.64 MHz, and a low THD of 1.29E-6%, hence supports the potential of wide applicability in analog communication. Similarly, the proposed pair with CC configuration produces approximately a unit current gain of 0.99 with wider bandwidth of 1.90 MHz and low THD of 1.76E-6%, therefore it can be used as a current buffer in a generalized current follower circuit. Conclusively, the device structure of this new BJT pair may be considered the third consecutive member of the series of Darlington pair and Sziklai pair. The layout of the proposed CE and CC amplifier occupy small areas of 158.30 μm2 (10.23×15.47 μm) and 141.16 μm2 (10.20×13.84 μm) respectively in 180 nm process technology.